Flow in a Permeable Channel with Effect of an Exponential Reabsorption at Walls - Varunkumar, M (Journal of Applied Nonlinear Dynamics, 2026)
This paper presents the steady flow of viscous incompressible fluid through a permeable channel with the effect of an exponential reabsorption at the walls. The fluid reabsorption across the channel walls is assumed by taking the flux as a function of axial length. The approximate solutions for velocity, mean pressure drop, wall shear stress and streamlines are solved by regular perturbation technique and finite difference method. The effect of reabsorption on the velocity profiles at different locations of axis, wall shear stress, mean pressure drop and streamlines are discussed through graphs. It is observed that the pressure drop and wall shear stress decrease as reabsorption increases. Further the streamlines show that the reabsorption significantly influences the flow pattern.